Peran Usaha Mikro Kecil Menengah (UMKM) Dalam Kebertahanan Ekonomi Keluarga Di Desa Pulo Dogom Kabupaten Labuhanbatu Utara - Nurul Huda (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2022)
This study discusses the role of Micro, Small and Medium Enterprises (Umkm) in Family Economic Sustainability in Pulo Dogom Village, North Labuhanbatu Utara. The purpose of this study was to find out how the role of Micro, Small and Medium Enterprises (Umkm) in Family Economic Survival in Pulo Dogom Village, North Labuhanbatu Utara. This study uses qualitative research with data collection techniques used are observation, interviews and documentation. Indepth interviews were conducted with selected informants. The results of this study indicate the role of micro, small and medium enterprises (Umkm) in the economic survival of families in the village of Pulo Dogom. This study intends to look at the role of micro, small and medium enterprises so that they can improve family economic survival for the welfare of employees. This study aims to determine the role of micro, small and medium enterprises on employee survival in Umkm Tahu Mas Tagor. The results of this study indicate that the existence of these Umkm has a very important role for the welfare of the community by opening up employment opportunities and increasing the income of the surrounding community so that they can meet their daily needs such as food, as well as other needs such as housing, family health and the need for children's education. brand subsidiaries and create job opportunities for the surrounding community to help improve the welfare of the community. In its implementation it is still said to be ineffective, this is because there are still many shortcomings that occur in finding solutions to the problems faced by entrepreneurs, especially in micro, small and medium enterprises, including capital so that the lack of manpower is caused by the lack of capital for UMKM actors which cause their business to run. Experienced ups and downs so that it affects production and income.